Mechanical behavior of honeycomb lattices manufactured by investment casting for scaffolding applications - Puga, Hélder (2017)
Lightweight metallic lattices in the form of honeycombs are long known to exhibit a good mechanical strength/weight relation, given their geometry and relative density, in comparison with bulk materials. Due to the current developments in additive manufacturing techniques, the production of honeycombs by investment casting is now easier and may be a competitive route when compared to welding and gluing of sheet metal. This study explores the importance of the manufacturing design when producing honeycombs by investment casting. It is shown by numerical simulation and experimental procedures that mold filling in directions where horizontal ribs are present may induce defects such as interdendritic porosities. These defects have a relevant role in the elastic domain of the lattices, decreasing the apparent Young's modulus and the plastic collapse stress. In terms of energy absorption, it is shown that these porosities have no significant effect due to the fragile fracture of both casting directions.